Factors that influence entrepreneurial intention among students Universiti Malaysia Kelantan (UMK) / Nur Intan Farahiah Abdull Muain - Abdull Muain, Nur Intan Farahiah (Bachelor of Finance (Hons), 2015)
Entrepreneurship is one of the field that can people take involve to get the income especially the student that basically take involve to get the side income. This survey is to determine the factors that influence the Entrepreneurial Intention among Students of Universiti Malaysia Kelantan (UMK). The objectives of this study are to investigate whether attitude, subjective norms and perceived behavioural control are the significant factor that influence the Entrepreneurial Intention among Students. The sample consists of 120 respondents from the Students of Universiti Malaysia Kelantan (UMK). The data used multiple linear regression method and analysed using SPSS 20.0. Based on the finding, attitude, subjective norms and perceived behavioural control are significant factor that influences Entrepreneurial Intention among Students of Universiti Malaysia Kelantan (UMK)